20-HETE Participates in Intracerebral Hemorrhage-Induced Acute Injury by Promoting Cell Ferroptosis - Han, Ranran; Wan, Jieru; Han, Xiaoning; Ren, Honglei; Falck, John R.; Munnuri, Sailu; Yang, Zeng-Jin; Koehler, Raymond C. (Frontiers in Neurology, 2021)
Intracerebral hemorrhage (ICH) is a highly fatal type of stroke that leads to various types of neuronal death. Recently, ferroptosis, a form of cell death resulting from iron-dependent lipid peroxide accumulation, was observed in a mouse ICH model. N-hydroxy-Nʹ-(4-n-butyl-2-methylphenyl)-formamidine (HET0016), which inhibits synthesis of the arachidonic acid metabolite 20-hydroxyeicosatetraenoic acid (20-HETE), has shown a protective effect after ICH. However, the underlying mechanisms of the neuroprotective effect need further investigation. We explored whether 20-HETE participates in ICH-induced ferroptosis ex vivo by using hemoglobin-treated organotypic hippocampal slice cultures (OHSCs) and in vivo by using a collagenase-induced ICH mouse model. Ex vivo, we found that the 20-HETE synthesis inhibitor HET0016 and antagonist 20-6,15-HEDGE reduced hemoglobin-induced cell death, iron deposition, and lipid reactive oxygen species levels in OHSCs. Furthermore, 20-HETE inhibition in OHSCs increased the expression of glutathione peroxidase (GPX) 4, an antioxidant enzyme that serves as a main regulator of ferroptosis. In contrast, the 20-HETE stable mimetic 20-5,14-HEDGE induced massive cell death in OHSCs that was significantly inhibited by the ferroptosis inhibitor ferrostatin-1. In vivo, HET0016 treatment ameliorated focal deficits, reduced lesion volume, and decreased iron accumulation around the lesion at days 3 and 7 after ICH. In addition, lipid peroxidation was decreased and expression of GPX4 was increased in the HET0016-treated ICH group. The mitogen-activated protein kinase pathway also was inhibited by HET0016 in vivo. These results indicate that 20-HETE contributes to ICH-induced brain injury in part by activating ferroptosis pathways, thereby providing an upstream target for inhibiting ferroptosis.